A smart monitoring system for campus using ZigBee wireless sensor networks - Allahham, Alaa Azmi; Rahman, Md. Arafatur (Penerbit UMP, 2018)
The wireless sensor networks are autonomous sensors that are distributed to monitor environmental and physical conditions and pass them across the network to other areas, which is considered one of the key elements that are used in the applications of smart cities. Therefore, this paper aims to provide a design to add more smart applications to the sanctuary and other compounds based on wireless sensor networks using ZigBee technology. The transition from reliance on the style of surveillance and controlled manually by staff to apply the principles of smart applications through wireless sensor network which provides the ability to getting all the necessary information and capabilities of controlling and monitoring are required to automatically and thus saving the time, effort, and money. The system proposed in this paper to design a smart monitoring system at the campus to control the opening and closing of the doors of many halls and the possibility of including lighting systems and appliances. The results obtained from OPNET program show that the network topology, which used within a ZigBee network vary in terms of performance, thus giving options for designers to build their network and choose technologies that suit their project.